Neolithic Polished Stone Artifacts: A Study of Sourcing and Mobility in Alentejo Region, Portugal - Fikeru, Sissay; Mirão, José; Valera, António; Beltrame, Massimo; Roseiro, José; Tsoupra, Anna; Moreira, Noel; Moita, Patrícia (Peer Beyond Graduate Research Conference, 2025)
This study examines the sourcing of amphibolite polished stone artifacts from Late Neolithic–Chalcolithic contexts at the Perdigões archaeological complex. The study analyzed archaeological artifacts alongside geological samples collected from the broader region, for straightforward comparison. Petrographic, mineralogical, and geochemical analyses reveal a clear mismatch between the artifacts and the geological samples collected within a 60-kilometer radius, indicating that the raw materials were not obtained from nearby sources.